First-principles studies of lithium storage in reduced graphite oxide - Robledo, Carla Belén (2014)
The present work performs a first-principles study of the lithiation of graphite oxides with low oxygen content, which resemble reduced graphite oxide materials. The chemical nature of the Li structure formed is analysed, leading to the conclusion that the nature of lithium binding in these materials is completely different from that observed in pristine graphite. The stability of the lithium structures formed under different loadings is studied, with the finding that the lithiation potentials predicted are within the ranges of the values observed experimentally.